2006
DOI: 10.1111/j.1420-9101.2005.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Does competitive divergence occur if assortative mating is costly?

Abstract: Most models of sympatric speciation have assumed that assortative mating has no costs. A few studies, however, have shown that the costs for being choosy can prevent such speciation. Here, we investigate the role of the strength of assortment and of the costs for being choosy for a simple genetic model of a single (‘magic’) trait that mediates both intraspecific competition for a continuum of resources and assortative mating, which is induced by choosy females who preferentially mate with males of similar phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 47 publications
4
66
0
1
Order By: Relevance
“…It is known that sexual selection has the potential to lead to the loss of variation in sexually selected traits across incipient species, eliminating reproductive isolation, and that this is more likely to occur if trait and preference frequencies are increasingly asymmetrical between the diverging types (15)(16)(17)(18)(19). Because our goal is to pinpoint the role of sexual selection in species maintenance when this maintenance occurs, we center our analyses on roughly symmetric starting conditions and focus (although not exclusively) on symmetric parameter values.…”
Section: Model and Resultsmentioning
confidence: 99%
“…It is known that sexual selection has the potential to lead to the loss of variation in sexually selected traits across incipient species, eliminating reproductive isolation, and that this is more likely to occur if trait and preference frequencies are increasingly asymmetrical between the diverging types (15)(16)(17)(18)(19). Because our goal is to pinpoint the role of sexual selection in species maintenance when this maintenance occurs, we center our analyses on roughly symmetric starting conditions and focus (although not exclusively) on symmetric parameter values.…”
Section: Model and Resultsmentioning
confidence: 99%
“…Whether assortative mating could evolve in this situation may depend on the biology of searching and the assumptions of the model; de Cara et al [22] found that the spread of an allele for assortative mating was uniformly inhibited by direct selection when they assumed lower mating success of rare individuals (but see, e.g. [9]; interestingly, a version of de Cara et al's model that does not induce sexual selection finds that assortment always evolves to completion provided that disruptive viability selection on the trait is present, unlike in, e.g. [12]; intermediate levels of assortment are not found in de Cara et al's models).…”
Section: Discussionmentioning
confidence: 99%
“…positive frequency-dependent selection), making it harder for sympatric speciation to occur. Similarly, Bü rger and coworkers [9,10,25] demonstrated that an intermediate level of assortment tends to deplete genetic variation in the trait that is the target of assortative mating, owing to the generation of locally stabilizing selection when rare types find it difficult to find mates (see also [35]). Although they did not study the evolution of assortment per se, they argue that this loss of variation would prevent further progress towards speciation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Schneider and Bürger (2005) showed that slight costs can still allow speciation to occur. Whether this conclusion implies that assortment can evolve with slight costs remains to be shown.…”
Section: ϫ2mentioning
confidence: 99%